Descriptive Study: Clinical and Histopathological Aspects of Ovarian Cyst in Tarakan Hospital Period 2020-2023 - Jamilah, Putri; Reni Angeline; Shintia Christina; Erma Mexcorry Sumbayak (Jurnal MedScientiae, 2025)
Ovarian cysts are a common gynecological condition that can be benign or malignant. Ovarian cysts are often asymptomatic, but can cause disruption of ovarian function and have the potential to develop into cancer. This study aims to determine the prevalence rate of ovarian cysts based on clinical and histopathological features at Tarakan District Hospital in the 2020-2023 period. This descriptive study used a cross-sectional design with data obtained from the anatomical pathology laboratory archives and medical records at Tarakan District Hospital. The research sample consisted of 427 subjects. The results of the study showed that the most common clinical picture was an enlarged abdominal lump (48.7%), the most common clinical diagnosis was ovarian cyst (25.5%), the most common histopathological diagnosis was endometriosis cyst (40.75%), and the most common age group was ≥19-<45 years old (52.7%). The analysis showed that the prevalence of ovarian cysts was highest in this age group, with endometriosis cysts as the most frequently found type based on anatomical pathology examination. Based on these results, it can be concluded that ovarian cysts most often occur at ages ≥19-<45 years with endometriosis cysts being the most common type.